Management of hypertrophic scars in adults: A systematic review and meta‐analysis. (31st January 2022) - Choi, Charles; Mukovozov, Ilya; Jazdarehee, Aria; Rai, Roopal; Sachdeva, Muskaan; Shunmugam, Maheshver; Zaslavsky, Kirill; Byun, Stephanie; Barankin, Benjamin
ABSTRACT: Hypertrophic scars (HTS) are elevated scars which occur due to abnormalities in wound healing after injury and may be associated with pain, pruritus and functional impairment. Despite multiple available treatment options, there is no universal approach to treating HTS. We searched the Web of Science (Core Collection), MEDLINE and EMBASE databases. Title, abstract and full‐text screening, along with data extraction, were performed in duplicate. Risk of bias was assessed using the Cochrane risk‐of‐bias tool. The Vancouver Scar Scale (VSS) scores and mean differences were used for meta‐analysis. We screened 3800 abstracts and included 34 randomised controlled trials evaluating treatments for HTS in adults. Silicone and laser modalities improved VSS scores by 5.06 (95% CI: 6.78, 3.34) and 3.56 (95% CI: 5.58, 1.54), respectively. Intralesional triamcinolone combined with silicone or 5‐fluorouracil was superior to intralesional triamcinolone monotherapy. Limitations of this study include exclusion of studies which did not utilise VSS, and pooling of studies based on common modalities. Further studies are needed to examine the efficacy of existing and emerging treatment modalities for HTS. Our study supports the treatment of HTS in adults with silicone gel or sheets, injected triamcinolone (preferably combined with 5‐fluorouracil or silicone products), pulsed dye laser and fractionated CO2 laser.